2017
DOI: 10.24875/ric.17002098
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Lung Pathology in Autopsies of Children with Cancer

Abstract: background: although pulmonary involvement is common in patients with cancer, its frequency and nature is seldom reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Diffuse alveolar hemorrhage, a rare but severe non‐infectious complication of hematopoietic cell transplantation (HCT), presents with respiratory failure and hemoptysis around the time of white blood cell engraftment, and is associated with a high mortality rate . A recent study on autopsies of children with cancer found a high incidence of pulmonary hemorrhage (40%), this being the most frequently missed clinical diagnosis . The absence of hemoptysis does not exclude a diagnosis of diffuse alveolar hemorrhage in adults; this may also be true for children.…”
Section: Cardiothoracic Oncologic Emergenciesmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage, a rare but severe non‐infectious complication of hematopoietic cell transplantation (HCT), presents with respiratory failure and hemoptysis around the time of white blood cell engraftment, and is associated with a high mortality rate . A recent study on autopsies of children with cancer found a high incidence of pulmonary hemorrhage (40%), this being the most frequently missed clinical diagnosis . The absence of hemoptysis does not exclude a diagnosis of diffuse alveolar hemorrhage in adults; this may also be true for children.…”
Section: Cardiothoracic Oncologic Emergenciesmentioning
confidence: 99%